Cyber Intelligence in Counterterrorism: AI-Powered Detection of Encrypted Jihadist Threats. - Berzinji, Ala (Journal of Human Security (Librello Publishing House), 2025)
Encryption offers a contradictory challenge of securely enabling communication yet allowing terrorist organizations, and particularly the jihadist organizations, to evade international counterterrorist surveillance systems. Such groups make extensive use of encrypted technologies for coordination of actions, sharing of propaganda, and illegal activities to avoid regular intelligence and cybersecurity standards. This paper discusses the innovative artificial intelligence (AI) and machine learning (ML) techniques for identifying and deciphering encrypted communications employed by the jihadist networks. A real-time analysis framework is proposed that uses deep learning models, unsupervised learning methods, and tools of natural language processing (NLP). To ensure replicability and practical implementation, a generalised algorithmic structure accompanied by pseudocode is included. The proposed system is evaluated using datasets derived from simulations, authentic scenarios, and extremist digital platforms, annotated through manual and automated methods. Comprehensive experimental results indicate that hybrid ML models can reliably flag suspicious communication patterns using only metadata, packet dimensions, and traffic flow characteristics, thus obviating the necessity for content access. The findings highlight AI's capacity to furnish intelligence agencies with novel capabilities for the proactive identification of encrypted terrorist activities, thereby reinforcing counterterrorism operations. The study further stresses the importance of continuous model refinement and ethical governance for responsible and effective deployment.